2021
DOI: 10.3390/pr9060912
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes with Caffeic Acid: Morphological and Structural Characterisation, Their Properties and Stability in Time

Abstract: Medical and pharmaceutical research has shown that liposomes are very efficient in transporting drugs to targets. In this study, we prepared six liposome formulas, three in which we entrapped caffeic acid (CA), and three with only phospholipids and without CA. Determination of entrapment efficiency (EE) showed that regardless of the phospholipids used, the percentage of CA entrapment was up to 76%. The characterization of the liposomes was performed using Dynamic Light Scattering (DLS), Atomic Force Microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Moreover, it was observed that the release of entrapped CA occurs gradually. In the first eight hours the release is at its high (over 80%), after which it is getting reduced 50 . Katuwavila et al 51 prepared caffeic acid-loaded egg phosphatidylcholine liposomes with a similar encapsulation efficiency of nearly 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was observed that the release of entrapped CA occurs gradually. In the first eight hours the release is at its high (over 80%), after which it is getting reduced 50 . Katuwavila et al 51 prepared caffeic acid-loaded egg phosphatidylcholine liposomes with a similar encapsulation efficiency of nearly 70%.…”
Section: Discussionmentioning
confidence: 99%
“…According to Caddeo et al 49 , in general, liposomal encapsulation is not significantly influenced by the lipids used for the preparation of the liposomes. Dejeu et al 50 determining of entrapment efficiency showed that, regardless of the composition of phospholipids (PC, DMPC and DPPC), the percentage of CA entrapment was up to 76%. Moreover, it was observed that the release of entrapped CA occurs gradually.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro release studies were conducted using the cellulose dialysis membrane diffusion technique, according to Dejeu’s work [ 23 ]. Prior to beginning the assay, cellulose dialysis membranes (Float-A-Lyzer G2, CE, 10 kDa, SpectrumLabs, Los Angeles, CA, USA) were equilibrated at 4 °C with ultrapure water for 12 h, which was replaced with PBS for 1 h. The donor chamber was filled with 1 mL of GA-loaded Tf-functionalized liposomes.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of liposomes containing CAPE, including size, zeta potential, PDI, and EE%, as well as their morphology, were determined. The results obtained from the EE% indicated that the liposomes were able to load a significant amount of CAPE, as per Dejeu et al37 This study employed HSPC, cholesterol, and DSPE-PEG2000 for the synthesis of liposomes. The efficiency of the liposome was found to increaseF I G U R E 5 The release percentage of (A) liposomal caffeic acid phenethyl ester (CAPE) and (B) free CAPE versus time at different pH values.…”
mentioning
confidence: 52%